GENDER PROFILE OF INCOME AND CONSUMPTION: EVIDENCE FROM THE NATIONAL TRANSFER ACCOUNTS OF MOLDOVA - Gagauz, Olga; Prohnitski, Valeriu (Economy and Sociology, 2022)
The use of the National Transfer Accounts (NTA) methodology has opened up the possibility of examining gender differences in income and consumption throughout the life cycle. This article presents the results of the study of the gender profile of income and consumption based on the NTA of Moldova for 2019. Moldova is characterized by a low level of employment of the population, low incomes and a high involvement of the population in international labor migration. Women's labor incomes are lower than men's throughout the life cycle, and the life cycle surplus is entirely formed by men, who are net donors to cover the life cycle deficit of other age groups during the working period. More than two-thirds of the economic life cycle deficit is held by women, and the gender gap in economic dependence was 22.7% - an additional share of the total labor income needed to finance women's economic dependence compared to the total labor income needed to finance men's economic dependence. Differences in the age profile of working income are due to the fact that women enter the labor market a little later than men, due to much higher enrollment rates in higher education institutions, as well as due to low participation in the labor market during the period associated with the birth and upbringing of children. The economic dependence of women is a reflection of the “gender contract” characteristic of Moldova, according to which a man and a woman participate in the labor market, but the woman still has most of the household chores.” It can be assumed that the problem of underestimation of income by the population in the household survey could cause an underestimation of the age profile of labor income, which, in turn, influenced the estimation of the size of the economic life cycle deficit.